Hukum Waris Islam (Telaah Pemikiran Muhammad Syahrur) - Laili, Afrohatul (SINDA: Comprehensive Journal of Islamic Social Studies, 2023)
One of the figures who contributed to criticism of inheritance law was Muhammad Syahrur (Syahrur). There is no doubt about Syahrur's controversy and influence in the Muslim world. He is a contemporary scholar who tries to re-read Islamic law and reconstruct it with contemporary readings, which often results in different results from those of the fuqaha in general. Syahrur made Syahrur's main contribution in the field of Ushul Fiqh, bringing major implications to various readings and conclusions of Islamic law including inheritance law which is different from the views of previous jurists. Apart from criticizing the jurists who placed the rules of wills under inheritance, Syahrur also dismantled the "rigid" system of dividing inheritance. For Syahrur, the division between men and women (namely 2:1) does not apply forever. Such provisions can change within certain limits. It is possible that under certain conditions, the share becomes 1:1. This research uses normative research because the research uses library materials as the main data for analyzing cases. This research examines more specifically the study of Muhammad Syahrur's thoughts on Islamic inheritance law. Syahrur believes that wills should be prioritized over inheritance, because they can better accommodate the values ​​of justice. Apart from that there is no text regarding the verses of the will, Syahrur's hudud theory also has implications for the collapse of the old view that parts of the inheritance cannot be changed at all. Syahrur's findings, on the contrary, are that the parts change and are dynamic. Syahrur often uses these two approaches in finding solutions to matters of inheritance and will. Apart from that, another unique thing about Syahrur's thinking is that he reconstructed Islamic inheritance law by getting out of the literal texts of Islamic teachings to find contextual inheritance law.